Super-Resolution Localisation of Nuclear PI(4)P and Identification of Its Interacting Proteome - Fáberová, Veronika; Kalasová, Ilona; Krausová, Alžběta; Hozák, Pavel (Cells, 2020)
Phosphoinositides are glycerol-based phospholipids, and they play essential roles in cellular signalling, membrane and cytoskeletal dynamics, cell movement, and the modulation of ion channels and transporters. Phosphoinositides are also associated with fundamental nuclear processes through their nuclear protein-binding partners, even though membranes do not exist inside of the nucleus. Phosphatidylinositol 4-phosphate (PI(4)P) is one of the most abundant cellular phosphoinositides; however, its functions in the nucleus are still poorly understood. In this study, we describe PI(4)P localisation in the cell nucleus by super-resolution light and electron microscopy, and employ immunoprecipitation with a specific anti-PI(4)P antibody and subsequent mass spectrometry analysis to determine PI(4)P's interaction partners. We show that PI(4)P is present at the nuclear envelope, in nuclear lamina, in nuclear speckles and in nucleoli and also forms multiple small foci in the nucleoplasm. Nuclear PI(4)P undergoes re-localisation to the cytoplasm during cell division; it does not localise to chromosomes, nucleolar organising regions or mitotic interchromatin granules. When PI(4)P and PI(4,5)P2 are compared, they have different nuclear localisations during interphase and mitosis, pointing to their functional differences in the cell nucleus. Mass spectrometry identified hundreds of proteins, including 12 potentially novel PI(4)P interactors, most of them functioning in vital nuclear processes such as pre-mRNA splicing, transcription or nuclear transport, thus extending the current knowledge of PI(4)P's interaction partners. Based on these data, we propose that PI(4)P also plays a role in essential nuclear processes as a part of protein-lipid complexes. Altogether, these observations provide a novel insight into the role of PI(4)P in nuclear functions and provide a direction for further investigation.
Keywords: Cell Cycle; jaderné proteiny; buněčné jádro; nádorové buněčné linie; Nuclear Envelope; Protein Binding; Nuclear Proteins; Phosphatidylinositol Phosphates; buněčné jadérko; Cell Line, Tumor; nucleus; Cluster Analysis; buněčný cyklus; jaderný obal; Cell Nucleus; fosfatidylinositolfosfáty; Proteome; PI(4)P; Humans; vazba proteinů; phosphoinositides; proteom; Cell Nucleolus; shluková analýza; lidé